Kendala Kelompok Simpan Pinjam Perempuan (SPP) Program Nasional Pemberdayaan Masyarakat (PNPM) Di Nagari Koto Baru Kec. Luhak Nan Duo Kabupaten Pasaman Barat.â Skripsi. Program Studi Pendidikan - Dayanti, Riwi - (Pendidikan Sosiologi, 2014)
PNPM program run by the government in Nagari Koto Luhak Nan Duo New District of West Pasaman assistance in the form of loans disbursed to the SPP target groups (womens credit). The funds were rolled for each target group tuition each member receives the funds amounting to 2-5 million / person. However, in practice the PNPM program has some problems or issues such as; still a lack of public understanding about rural independent PNPM program, the lack of understanding of the meaning of SPP joint responsibility, delays in payments on the SPP on the PNPM program. The theory used in this study is the theory of structural functionalism. This theory is the idea of a social life as a system, a network of different sections, explaining part of the structure. This research is categorized into types of qualitative research approaches. This type of research used in this research is descriptive. The criteria for the informants in this study were 1) people who are members of the SPP on PNPM in Nagari Koto Baru, with troubled loans. 2) Board of PNPM in Nagari Koto Baru. Data to be collected in this study are primary and secondary data obtained through the data collection methods such as interviews. The unit of analysis is the group with the analysis of the data comprising the steps of reduction, data presentation / analysis of data, and drawing conclusions. The results of the study can be summarized as follows: 1) Implementation of PNPM program implemented in Nagari Koto Baru has some obstacles or problems such as; still a lack of public understanding about rural independent PNPM program, the lack of understanding of the meaning of SPP joint responsibility, delays in payments on the SPP on the PNPM program. 2) The solution in solving problems experienced by the target group in Nagari Koto Baru PNPM is to establish agreed sanctions upon deliberation between villages (MAN) are sanctions and penalties Kenagarian Kejorongan. Additionally UPK (Activity Management Unit) PNPM in Nagari Koto Baru give IPTW (Incentive Payments On Time) in the form of money, certificates and trophies to the SPP who pay the installment on time.